Tverrprofesjonell klinisk praksis for helsefagstudenter som en del av den ordinære praksisperioden, En casestudie fra en akutt geriatrisk-, slag - og rehabiliteringsavdeling - Kristensen, Dorte Vesterager; Flo, Jill; Fagerström, Lisbeth (Nordisk tidsskrift for helseforskning, 2014)
Interdisciplinary Professional clinical practice for health sciences students as part of the regular work placement- a casestudy from an acute geriatric - stroke and rehabilitation department. This study describes students’ experiences of interdisciplinary clinical practice (ICP) in an emergency department of geriatrics, stroke and rehabilitation in Norway. The purpose of this study was to investigate whether ICP has contributed to the students’ knowledge of their own and other professional’ expertise and expanded understanding of patients’ rehabilitation needs. 19 students; nursing, occupational therapist, physiotherapist and social worker students were represented in the study. A model with various learning activities was developed in collaboration between two university colleges and the department. ICP lasted two weeks during a regular practice period. Students’ experiences were evaluated through focus group interviews. The study concludes that collaboration in patient situations is essential for the students awareness of each other’s disciplines, expanded perspective on own subjects and the patients need of rehabilitation. The short length of stay in the department led to increased focus on interaction early in the patient care.